The Vasopressin System and Behavior - Heather K. Caldwell (Frontiers Research Topics, 2018)
Vasopressin and its homologues are evolutionarily ancient neuropeptides that are important to the neural modulation of behavior in many species. Over the last several decades there has been an emergence of cross-species consensus with regards to the broad behavioral domains that the vasopressin system influences. However, there are nuanced species- and sex-differences in the functions of this system, as well as evidence for cross-talk between this system and the oxytocin system. For this Research Topic, reviews and research articles from investigators across the field were solicited, with the goal to highlight some of the complexity and diversity within this system. This collection challenges researchers to broaden their understanding of this system as well as identifies areas in which additional research is needed. Topic areas featured include: - System complexity - Sex and species differences - Developmental effects - Human and non-human primates.